Low temperature synthesis, dielectric and electrical characteristics of Bi2/3Cu3−xNi xTi4O12(where x = 0.05, 0.1, and 0.2) ceramics for the dielectric and electrical properties - Rai V.S.; Prajapati D.; Kumar V.; Verma M.K.; Pandey S.; Das T.; Singh N.B.; Mandal K.D. (My University, 2025)
We have investigated a low-temperature chemical route of the synthesis and measured the dielectric, electrical and morphological characteristics of the Ni-doped BCTO ceramic (Bi2/3Cu3−xNixTi4O12 where x = 0.05, 0.1, and 0.2) compound. The synthesized material was heated at 1123 K for 8 h in this research study. The uniform phase formation of the material was confirmed by the X-ray diffraction pattern, scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy studies. The dielectric constant was observed to be 6902 at 470 K and 100 Hz. The tangent loss (tan δ) value for BCNTO-0.1 ceramic was obtained to be 0.08 at 310 K and 10 kHz. X-ray photoelectron spectroscopy was used to confirm the ceramic’s oxidation condition. The electrical conductivity of Bi2/3Cu3−xNixTi4O12 (where x = 0.05, 0.1, and 0.2) ceramics fluctuate with temperature in the range of 300–500 K, satisfying the Arrhenius equation and producing a nearly single slope. The calculated specific capacitances of BCNTO-0.05, BCNTO-0.1, and BCNTO-0.2 based electrodes are 71 F/g, 38 F/g, and 32 F/g, respectively. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.